Urgensi Sertifikasi Halal dalam Pemberdayaan Ekonomi Perempuan - Fauziah Fauziah; Sappeami Sappeami; Nur Afiah; Hiljati Hiljati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Halal certification has great urgency in ensuring the availability of products that conform to the principles of the Islamic religion and the needs of Muslim consumers, as well as facilitating access to the rapidly growing global market. Halal certification can be an important tool in empowering women, by providing access to them in industry, expanding skills and knowledge, and improving health and food safety for families and communities moreover it is very helpful in improving family welfare. With the assistance of halal certification carried out by the government for free, this affects the number of halal products that exist. This research aims to understand in depth how the urgency of halal certification in empowering women. The method used is qualitative research. The results showed that the urgency of halal certification in empowering women can reduce the obstacles faced by women entrepreneurs with several appropriate strategies to overcome these obstacles, halal certification not only provides commercial benefits for women entrepreneurs, but also has the potential to empower them economically and improve the welfare of society as a whole.